The Determinants of Extreme Poverty Among Working Households in East Java - Maulana, Royan Gilbran; Febri Putranto, FX Gugus; Deffinika, Ifan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
East Java Province is one of the provinces with an extremely poor population in Indonesia. The purpose of this study is to identify the factors that explain the effect of poverty, specifically on working households, which are expected to provide insights into policies to alleviate extreme poverty in East Java. This study uses microdata from the 2022 National Socioeconomic Survey (Susenas) at the household level in East Java, which has 38 districts/cities. By using binary logistic regression analysis, the results show that gender, education, marital status, age generation, employment status, and business field of the head of the household have a significant effect on the chances of becoming an extremely poor household. Furthermore, special policies are needed related to demographic and employment factors at the household level in alleviating extreme poverty in East Java.